THE ATTITUDES AND INTERESTS OF FEMALE STUDENTS FOR THE TEACHING CONTENTS AND THE CLASSES OF PHYSICAL EDUCATION - Goran Šekeljić; Milovan Stamatović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
In this paper, using as a sample of 142 fourth-grade female pupils from three primary schools in Uzice and Pozega, their interests for physical education classes and the teaching contents in this subject have been examined. The results of the research point to the fact that the girls of this age are interested in basketball, handball and football. This fact should be considered when making the teaching curricula The results of the research point to the fact that the girls of this age like physiacal education and that it is their favourite school subject. On the basis of that fact it is possible to draw an indirect conclusion that the classes have been realized on the methodological level which presupposes obtaining the highest goal of physical education, and that is being involved in physical activity.